Schizophrenia and Nicotine - A Bittersweet Psychiatric Story - Satrajit Ghosal; Ankit Halder; Sarthak Keshri; Navna Panchami Ravindran; Akhil Joshi (Annals of Indian Psychiatry)
Background: Schizophrenia is a chronic mental disorder affecting mood, perception, and most importantly cognition. This severely interferes with the functioning of such patients. On the other hand, nicotine use (both smoke and smokeless tobacco) is very much prevalent in schizophrenic patients, much more than normal population. This study aims to find the relation between nicotine use and cognition in schizophrenic patients. Methodology: Fifty-six new patients diagnosed with schizophrenia of both sexes between ages 18 and 60 years, giving valid and informed consent, were selected for the study. Fagerstrom test for nicotine dependence was done and the patients were divided into two groups: scores 4 or less (low-to-moderate dependence) and scores 5 or more (severe dependence). The Cognitive Assessment Interview was performed. Then, an independent sample t-test was used to compare the scores on various cognitive domains between the two groups. Results: The cognitive scores were better in the group with severe tobacco dependence, both globally and across individual domains. These associations were statistically significant (P = 0.001). The mean difference was highest in the social cognition group. Among all the domains, the t-value was highest for the speed of processing domain, indicating that this particular cognitive domain has the best discriminative value when compared between two groups of nicotine users. Conclusions: Hence, to conclude, whether nicotine has indeed a beneficial effect on cognition in schizophrenia has to be investigated longitudinally so that a possible treatment option to address cognitive impairment in schizophrenia is obtained. Extensive longitudinal studies needs to be conducted to better understand the long-term effect of tobacco use and cognition in schizophrenia patients.